1969
DOI: 10.1128/aem.18.2.166-173.1969
|View full text |Cite
|
Sign up to set email alerts
|

Control of Byssochlamys and Related Heat-resistant Fungi in Grape Products

Abstract: Heat-resistant strains of Byssochlamys fulva, B. nivea, and other heat-resistant fungi were isolated from vineyard soil, grapes, grape-processing lines, and waste pomace. They are known to remain in grape juice occasionally and to grow in grape juice products. Ascospores of these fungi have a D value (decimal reduction time) of about 10 min at 190 F (88 C), but in the presence of 90 Bliters of SO2 per liter (normally added to the juice) the D value was cut in half. Filtration through a commercial diatomaceous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Bayne and Michener (1979) studied heat resistance of B. fulva in a defined medium consisting of 16Њ Brix glucose and 0.033M tartaric acid and calculated 3 log 10 inactivation times of 1.2 to 46 min at 90ЊC. King et al (1969) reported a B. fulva heat resistance of D 87.8ЊC of 11.3 min in grape juice. Some strains of B. fulva have reported D-values at 90ЊC of 1 to 12 min (Scott and Bernard, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Bayne and Michener (1979) studied heat resistance of B. fulva in a defined medium consisting of 16Њ Brix glucose and 0.033M tartaric acid and calculated 3 log 10 inactivation times of 1.2 to 46 min at 90ЊC. King et al (1969) reported a B. fulva heat resistance of D 87.8ЊC of 11.3 min in grape juice. Some strains of B. fulva have reported D-values at 90ЊC of 1 to 12 min (Scott and Bernard, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of asci Byssochhmys fulva NRRL 3493 asci were produced by the method of King et al (1969) except that the mould was grown in 1 1 fermentation flasks instead of in flat sided bottles. All experiments described were done with intact asci.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the rarity of B. fulva ascospores in foods, a minimal heat treatment is suggested for acidic foods (Maunder, 1969). The heat resistance of the ascospore is sufficiently high (King, Michener & Ito, 1969) for heavier than normal contaminations to cause food spoilage problems.…”
mentioning
confidence: 99%
“…It used to be thought that no development of moulds or bacteria of the genus Bacillus was possible in, for instance, canned or other packaged foods because of the existing vacuum, usually 45-25 cm Hg residual pressure, corresponding with a PO, of 90-50 mm. But fungi which actively spoil fruits, fruit juices or agricultural staples have been shown to develop in a PO, of c. 50-10 mm (Tabak & Cooke, 1968; Sanders, Davis & Diener, 1968;King, Michener & Ito, 1969) arid a Xeromyces sp.…”
Section: (Ii) Gaseous Environmentmentioning
confidence: 99%